2021
DOI: 10.1155/2021/9940009
|View full text |Cite
|
Sign up to set email alerts
|

Endangered Lymphocytes: The Effects of Alloxan and Streptozotocin on Immune Cells in Type 1 Induced Diabetes

Abstract: Alloxan (ALX) and streptozotocin (STZ) are extensively used to induce type 1 diabetes (T1D) in animal models. This study is aimed at evaluating the differences in immune parameters caused by ALX and STZ. T1D was induced either with ALX or with STZ, and the animals were followed for up to 180 days. Both ALX and STZ induced a decrease in the total number of circulating leukocytes and lymphocytes, with an increase in granulocytes when compared to control mice (CT). STZ-treated mice also exhibited an increase in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 83 publications
0
1
0
2
Order By: Relevance
“…The total WBCs count, lymphocytes and monocytes were significantly decreased, while granulocytes were significantly increased compared with diabetic control group and normal control group. These results are line with Queiroz et al [24], which suggested the administration of alloxan into the animals caused a decrease in lymphocytes and in general, the total number of circulating leukocytes, while granulocytes increased.…”
Section: Discussionsupporting
confidence: 92%
“…The total WBCs count, lymphocytes and monocytes were significantly decreased, while granulocytes were significantly increased compared with diabetic control group and normal control group. These results are line with Queiroz et al [24], which suggested the administration of alloxan into the animals caused a decrease in lymphocytes and in general, the total number of circulating leukocytes, while granulocytes increased.…”
Section: Discussionsupporting
confidence: 92%
“…Inhibition of glucokinase reduces glucose oxidation and ATP generation, thereby suppressing the ATP signal that triggers insulin secretion [ 12 ]. Alloxan monohydrate can induce type 1 diabetes [ 15 ]. In a few reported studies, induction of diabetes was based on the combination of STZ with a high-fat diet (STZ/HFD) [ 16 ] or carried out on genetically modified animals with diabetes (leptin receptor-deficient (Leprdb/JNju, db/db) mice) [ 17 ].…”
Section: Herbal Products and Their Active Constituents Used For Diabe...mentioning
confidence: 99%
“…BioBreeding ou BB (BioBreeding Diabetes Prone BB-DP rats), e pela indução química experimental de diabetes utilizando agentes chamados 20etonuria20ico -aloxana (ALOX) e a estreptozotocina (STZ) (GRAHAM; SCHUURMAN, 2015;QUEIROZ et al, 2021).…”
Section: Modelo Experimental De Dm1unclassified
“…Os animais não diabéticos receberam apenas solução fisiológica pela mesma via. Somente foram considerados animais diabéticos, aqueles que apresentaram glicemia superior a 300 mg/dL(QUEIROZ et al, 2021; e SPILLER et al, 2012).4.Aldrich), com 20% de soro fetal bovino (SBF) (Sigma Chemical Co, St. Louis, Mo, USA) e 30% de indutor de diferenciação de macrófagos obtidos de meio condicionado da cultura do cultivo de fibroblastos L929 (LCCM), durante sete dias, onde no quarto dia, foi feita a suplementação da cultura…”
unclassified